Surface Properties of Carbonaceous Solids as Examined by H NMR Spectroscopy Using the Bulk Freezing Procedure - V.V. Turov; R. Leboda; V.I. Bogillo; J. Skubiszewska-Zieba (Adsorption Science & Technology, 1996)
It has been established that the type of adsorption sites on the surface of different carbonaceous materials [graphite oxide, thermo-expanded graphite, graphitized and non-graphitized carbons, carbon black, carbonated silicas (Carbosils)] can be determined using a chemical shift in the 1 H NMR spectra of adsorbed test compounds possessing different donor–acceptor properties and polarizability. This is due to the existence of local magnetic anisotropy regions near the carbon surface. The 1 H NMR measurements on adsorbent/adsorbed water/inert solvent interfaces provide an effective procedure for the differentiation of NMR signals from molecules bound with various types of surface sites. Variations in the free energy of water in the adsorption layer of Carbosils having different carbon contents on the silica surface and their free surface energy have been determined from measurements of the temperature dependence of the NMR signal for non-freezing water in the cooling process. A low degree of carbonization for the initial silica surface leads to a drastic increase in the aqueous interlayer thickness structurized by the surface.